Political forms of modern society - "Lefort, Claude" (Cambridge, 1989)
Claude Lefort is one of the leading social and political theorists in France today. This anthology of his most important work published over the last four decades makes his writing widely accessible to an English-speaking audience for the first time. With exceptional skill Lefort combines the analysis of contemporary political events with a sensitivity to the history of political thought. His critical account of the development of bureaucracy and totalitarianism in the Soviet Union and Eastern Europe is a timely contribution to current debates about the nature and shortcomings of these societies. His incisive analyses of Marx's theory of history and concept of ideology provide the backdrop for a highly original account of the role of symbolism in modern societies. While critical of many traditional assumptions and doctrines, Lefort develops a political position based on a reappraisal of the idea of human rights and a reconsideration of what "democracy" means today. The Political Forms of Modern Society is a major contribution to contemporary social and political theory. The volume includes a substantial introduction that describes the context of Lefort's writings and highlights the central themes of his work.
Keywords: Bureaucracy